Bukit Merah Lake Contour Mapping Using Swarm Of Mini ASVs. - Abidin, Zulkifli Zainal; Abdul Rahim, Khairul Izman; Arshad, Mohd Rizal; Ngah, Umi Kalthum (2010)
Abstract- A new concept of an Autonomous Surface Vehicle (ASV) is proposed, mimicking the predictable biological balancing nature of the Drosophila or the fruit fly.